Fish dispersal in flowing waters: A synthesis of movement‐ and genetic‐based studies - Lise Comte; Julian D. Olden (Fish and Fisheries, 2018)
Enhancing our understanding of fish dispersal is central to the success of modern‐day conservation efforts in freshwater ecosystems. However, methods seeking to estimate dispersal are diverse; ranging from direct estimation of individual movements, computation of dispersal kernels, to indirect assessment using measures of gene flow across riverscapes. An important question is whether results from these different approaches provide a consistent picture of the spatial scales of dispersal. Here, we performed a review and meta‐analysis of the literature reporting both individual movements and genetic data to characterize patterns of dispersal for riverine fishes globally. Across all the studies considered ( N direct = 206; N indirect = 205), our results suggest restricted magnitudes of dispersal for riverine fishes, but highlight a large heterogeneity among species, taxonomic orders and geographies. For instance, we found that the maximum parent–offspring dispersal distances varied from 69 m to 1,086 km (median = 12 km; N species = 107), whereas the dispersal spread derived from isolation‐by‐distance slopes ( σ IBD ) from genetic data ranged from 19 m to 250 km (median = 1 km; N species = 56). Comparisons of species‐specific values also revealed significant and positive relationships between direct and indirect estimates of dispersal distances, indicating that organismal movement ability often translates into effective transmission of genes. Finally, this global overview pointed to important geographic and taxonomic disparities in the study of dispersal for riverine fishes. We thus encourage researchers to broaden the taxonomic and geographical scope of future investigations and identify emerging research frontiers where new scientific efforts are needed.